Perlindungan Hukum Kreditur Selaku Penerima Fidusia Atas Jaminan Fidusia Berupa Truk yang Disita Untuk Negara (Studi Putusan Pengadilan Tanjung Redeb Nomor:9/PDT.BTH/2019/PN.TNR) - Dwiandi Adam, Achmad Ricky; Adam, Richard C. (UNES Law Review, 2024)
A number of regulations include legal protection for legal subjects, both preventive and enforcement, which can be in the form of written or unwritten regulations. In the context of selling objects used as fiduciary collateral, creditors can be legally protected if the state confiscates the object. Fiduciary, essentially, involves transferring ownership rights to an item in the belief that the owner of the item will retain control of it. However, the state can confiscate items that are the subject of fiduciary guarantees if they are used for unlawful activities. Attention to this matter is important for finance companies which may experience losses due to state confiscation of objects used as fiduciary collateral.